An Item Bank for Abuse of Prescription Pain Medication from the Patient-Reported Outcomes Measurement Information System (PROMIS(®)) - Pilkonis, Paul A. (Pain Med, 2017)
Objective. There is a need to monitor patients receiving prescription opioids to detect possible signs of abuse. To address this need, we developed and calibrated an item bank for severity of abuse of prescription pain medication as part of the Patient-Reported Outcomes Measurement Information System (PROMIS(®)). Methods. Comprehensive literature searches yielded an initial bank of 5,310 items relevant to substance use and abuse, including abuse of prescription pain medication, from over 80 unique instruments. After qualitative item analysis (i.e., focus groups, cognitive interviewing, expert review, and item revision), 25 items for abuse of prescribed pain medication were included in field testing. Items were written in a first-person, past-tense format, with a three-month time frame and five response options reflecting frequency or severity. The calibration sample included 448 respondents, 367 from the general population (ascertained through an internet panel) and 81 from community treatment programs participating in the National Drug Abuse Treatment Clinical Trials Network. Results. A final bank of 22 items was calibrated using the two-parameter graded response model from item response theory. A seven-item static short form was also developed. The test information curve showed that the PROMIS(®) item bank for abuse of prescription pain medication provided substantial information in a broad range of severity. Conclusion. The initial psychometric characteristics of the item bank support its use as a computerized adaptive test or short form, with either version providing a brief, precise, and efficient measure relevant to both clinical and community samples.